Análisis molecular de pacientes pediátricos con leucemia linfoblástica aguda de estirpe B - Figueroa Padilla, Jesica (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
To detect any molecular alteration, provides additional information for a more specific diagnosis and the application of treatments dependent on the type of alteration. Objectives: To analyze the expression of TEL/AML1 , MLL - AF4 , BCR / ABL transcripts and E2A/PBX in children with acute lymphoblastic leukemia. Material and Methods : The study includes the detection of different translocations in bone marrow samples by RT -PCR method , RNA extracted from the samples. Results: A total of 27 samples were analyzed for the identification of molecular markers by RT -PCR. 8 Positive samples for obtaining the gene of TEL-AML1 fusion , of which three were positive by simple PCR and nested PCR 5 ; 3 samples positive for the fusion gene MLL- AF4 , where two were positive for one single PCR and nested PCR ; Two positive for the fusion gene E2A- PBX1 , sample 1 sample was positive by PCR for single and 1 nested PCR ; no sample was positive for BCR -ABL . Conclusion : The frequency of TEL- AML1 in our study is consistent with international reports while poor prognostic markers such as MLL- AF4 and E2A- PBX1 are found with high frequency in comparison with international reports . No case presented more than two molecular alterations , only expressed one.

Al detectar alguna alteración molecular, aporta información adicional para un diagnóstico más específico, así como a la aplicación de tratamientos dependientes del tipo de alteración. Objetivos: Analizar la expresión de los transcritos TEL/AML1, MLL-AF4, BCR/ABL y E2A/PBX en niños con leucemia linfoblástica aguda. Material y Métodos: El estudio incluye la detección de las diferentes translocaciones en muestras de medula ósea por el método RT-PCR, a partir del RNA extraído de dichas muestras. Resultados: Un total de 27 muestras han sido analizadas para la identificación de los marcadores moleculares mediante RT-PCR. Obteniendo 8 muestras positivas para el gen de fusión TEL-AML1, de las cuales 3 resultaron positivas por PCR simple y 5 por PCR anidada; 3 muestras positivas para el gen de fusión MLL-AF4, donde 2 resultaron positivas por PCR simple y 1 por PCR anidada; 2 muestras positivas para el gen de fusión E2A-PBX1, 1 muestra resulto positiva por PCR simple y 1 por PCR anidada; ninguna muestra resulto positiva para el gen de fusión BCR-ABL.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2013-1158; Análisis molecular; Pacientes pediátricos; Leucemia linfoblástica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2948